Socio-economic status of fishermen community of Wular Lake in district Bandipora of Jammu and Kashmir - Neelofer Habib; Salima Jan (Journal of Fisheries, 2021)
The present study investigates the socio-economic status of fishermen community of Wular Lake in district Bandipora of Jammu and Kashmir. Data were collected through structured interview schedule from 150 respondents from fishermen community between July and September 2020. It was found that 34.7% of the respondents fall in to the age group of 41–50 years and 56.0% were married. Majority of the respondents were illiterate (61.3%) and over half of the respondents (59.3%) earned monthly Rs.1000–5000. The study also explored that 93.3% of the respondents lived in their owned houses. The family size of fishing community was usually consisted of 7–10 members and 51.3% of them lived in a joint family system. However, most of them (54.66%) were dependent on river/canal water as drinking source and 59.3% were having dry latrine. It may be concluded that the fishermen community in the study area was the disadvantaged group of the society. Government, NGOs and respective stakeholders should come forward to take proper and necessary steps to improve their living conditions.